Performance Analysis of Bit-Error-Rate and Channel Capacity of MIMO Communication Systems over Multipath Fading Channels - Isiaka Ajewale Alimi; Jide Julius Popoola; Kayode Francis Akingbade; Michael O. Kolawole (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
In wireless communication systems (WCS), channel characteristics are random and unpredictable. The resultant effect of the randomness is the multipath effect that leads to multipath fading. Multipath fading is a major contributor to the unreliability of wireless communication links. In this paper, Multiple-Input, Multiple-Output (MIMO) schemes were investigated in mitigating the effect of signal fading. Space-time coded MIMO-OFDM was developed to enhance the performance of the WCS. The performance of the developed space-time coded MIMO-OFDM over both flat and frequency selective channels were compared with that of conventional WCS. The simulation results show that the space-time coded MIMO-OFDM considerably reduced the effect of multipath fading in WCS with improved bit error rate (BER) value.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.2014